Brief research report optimization of catalyst porosity arrangements for hydrogen production in microchannel reactors by methanol reforming - Chen, Junjie; Yu, Yehao (Frontiers in Energy Research, 2023)
Optimization of catalyst porosity arrangements is carried out for hydrogen production through computational modeling of a thermally integrated microchannel reactor. The reactor has parallel flow channels for conducting simultaneous oxidation and reforming reactions. Numerical simulations are performed under a variety of velocity conditions to evaluate the effect of reforming catalyst porosity arrangement on the transport phenomena in the reactor system. The oxidation catalyst has a uniform porosity, and the porosity range of the reforming catalyst is from 30 to 70 percent. The porosity is uniform in each segmented region and the overall porosity is maintained 50 percent. The heat and mass transfer issues for the reactor system are highly complex. Performance comparisons are made in terms of methanol conversion, hydrogen yield, and heat of reaction between these porosity cases under different inlet velocity conditions. Dimensionless Nusselt and Sherwood number analyses are performed to understand the underlying cause for the performance difference. The dimensionless numbers in transport phenomena are principally analyzed to understand how important the transverse transport components are. The results indicate that optimization of catalyst porosity arrangements is required for thermal matching purposes. The optimum porosity arrangement depends upon the flow rates. The catalyst porosities must be configured to improve the kinetics in the upstream or downstream sections of the reactor so that the endothermic and exothermic processes are thermally matched. While advantages can be realized by using the two-segment design, the three-segment design yields no advantage. The processes of transverse transport are of great importance to the chemical reactions.